Anodic Oxidation and Electropolimerization of Salicylic Acid - Lárez, Cristóbal; Márquez, Olga P.; Márquez, Jairo (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Electrochemical oxidation of salicylic acid is highly dependent on acidity of the electrolytic medium, due to the coexistence between protonated species, neutral species, carboxylate ions and phenoxy ions. Prevalence of one of these species, at a given pH, could explain the variation of the potential as acidity varies. In basic medium, oxidation of both carboxylate and phenoxy species takes place, while for weakly acidic or neutral media, the main reaction product is a thin resistive film that grows slowly onto the electrode surface. Ex situ FTIR reflectance measurements suggest the presence of aromatic ring segments linked by C Â¾ O Â¾ C and C Â¾ C bonds. In situ FTIR spectra show that C Â¾ C bonds appear slowly during the film growth. Initial resistivity of the film has been estimated using the model developed by Scharifker, and it was found to be within the range (1.6-2.4) 1011 W cm”“1